The Role of Slr0151, a Tetratricopeptide Repeat Protein from Synechocystis sp. PCC 6803, during Photosystem II Assembly and Repair - Rast, Anna; Rengstl, Birgit; Heinz, Steffen; Klingl, Andreas; Nickelsen, Jörg (Frontiers in Plant Science, 2016)
The assembly and repair of photosystem II (PSII) is facilitated by a variety of assembly factors. Among those, the tetratricopeptide repeat (TPR) protein Slr0151 from Synechocystis sp. PCC 6803 (hereafter Synechocystis) has previously been assigned a repair function under high light conditions (Yang et al., 2014, J. Integr. Plant Biol. 56, 1136-50). Here, we show that inactivation of Slr0151 affects thylakoid membrane ultrastructure even under normal light conditions. Moreover, the level and localization of Slr0151 are affected in a variety of PSII-related mutants. In particular, the data suggest a close functional relationship between Slr0151 and Sll0933, which interacts with Ycf48 during PSII assembly and is homologous to PAM68 in Arabidopsis thaliana. Immunofluorescence analysis revealed a punctate distribution of Slr0151 within several different membrane types in Synechocystis cells.